2014
DOI: 10.1007/s00894-014-2535-7
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic and nonlinear optical properties of triarylamine helicenes: a DFT study

Abstract: This work involved the design of a new series of triarylaminehelicenes (TAH) with significant hole transport capacity and enhanced nonlinear optical response. The geometries, electronic properties and nonlinear response of TAH derivatives were studied using density functional theory at the B3PW91/6-311++G (2d, 2p) level. Charge transfer and nonlinear optical response were analyzed and correlated with modifications in geometry and energy levels. Calculations indicated that trivial changes in the torsional angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 79 publications
0
21
1
Order By: Relevance
“…We have observed that k h (reorganisation energy for hole transport) values are comparatively smaller as compared to the k e (reorganisation energy for electron transport) values demonstrating relevance of studied helical derivatives as p-type material for Organic Light Emitting devices. k h for TOH and TTH molecules are found lower than those reported for triarylamine helical systems [36]. Lin et al [60], have calculated the reorganization energies of Alq3 for hole and electron transport to be 0.242 and 0.276 eV, respectively.…”
Section: Frontier Molecular Orbitals Uv-visible Spectra Charge Trancontrasting
confidence: 48%
See 2 more Smart Citations
“…We have observed that k h (reorganisation energy for hole transport) values are comparatively smaller as compared to the k e (reorganisation energy for electron transport) values demonstrating relevance of studied helical derivatives as p-type material for Organic Light Emitting devices. k h for TOH and TTH molecules are found lower than those reported for triarylamine helical systems [36]. Lin et al [60], have calculated the reorganization energies of Alq3 for hole and electron transport to be 0.242 and 0.276 eV, respectively.…”
Section: Frontier Molecular Orbitals Uv-visible Spectra Charge Trancontrasting
confidence: 48%
“…The enhancement of b value for TTH as compared TOH also correlated with increased u ge and decreased excitation energy of former as compare to later, thus following the Oudar and Chemla two level model [66]. It is worth noting that TOH and TTH helical systems shows higher value of second order hyperpolarizability as compared to already used material for NLO devices [36,67]. In addition to it the effective pconjugation in TOH and TTH helical will cause ring current in these system, thus will display NLO activity even in absence of external field.…”
Section: Frontier Molecular Orbitals Uv-visible Spectra Charge Tranmentioning
confidence: 57%
See 1 more Smart Citation
“…Conjugated organic systems are principally explored as hole transport materials for the organic light emitting devices (Fink et al, 1998; Jurchescu et al, 2004; Park et al, 2011; Tao et al, 2011; Kim et al, 2013; Wu et al, 2014; Islam and Pandith, 2014b; Fan et al, 2015). Because of troublesome processbility and instability in air, the exploration, design and synthesis of electron transport material has remained a significant challenge and hot stock within the field of organic electronics (Pandith and Islam, 2014; Zhao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Because of troublesome processbility and instability in air, the exploration, design and synthesis of electron transport material has remained a significant challenge and hot stock within the field of organic electronics (Pandith and Islam, 2014; Zhao et al, 2014). Within the recent years, conjugated nitrogen containing organic derivatives have been found as promising n-type or p-type materials for the fabrication of OLED (Fink et al, 1998; Jurchescu et al, 2004; Park et al, 2011; Tao et al, 2011; Kim et al, 2013; Pandith and Islam, 2014; Wu et al, 2014; Zhao et al, 2014; Islam and Pandith, 2014b; Fan et al, 2015). The material acquires this property because of their excellent optoelectronic properties, good oxidation and thermal stabilities, large electron affinities and high electron mobilities.…”
Section: Introductionmentioning
confidence: 99%